Inferior ST-Segment Elevation Pattern as a Result of a Small Bowel Obstruction: A Case Report - Ryu, Andrew; J. Jacobs, Andrew; Mastanduono, Andrew; Frank, Daniel; Garra, Gregory; C. Lee, Christopher (Archives of Academic Emergency Medicine, 2025)
ST segment elevation patterns on Electrocardiogram (ECG) are a crucial finding in the diagnosis and treatment of acute coronary syndrome. An ST segment elevation pattern can be a sign of acute myocardial ischemia requiring immediate intervention. However, ST elevation patterns have been reported to occur due to obstructive intraabdominal pathology, a diagnosis often confirmed by cardiac catheterization. Here we report a 75-year-old female who presented to the emergency department with worsening chest and epigastric abdominal pain. ECG demonstrated ST-segment elevations in inferior leads (II, III, and aVF) with reciprocal changes in the lateral leads (I and aVL). Physical exam was suggestive of a bowel obstruction at the site of a large incarcerated ventral hernia, which was later confirmed by imaging. Due to the lack of typical chest pain symptoms and a strong suspicion of obstructive intraabdominal pathology, activation of the catheterization laboratory was deferred. Decompression of the bowel obstruction was achieved with a nasogastric tube, which resulted in immediate resolution of ST-segment elevations. During her admission, her ventral hernia was repaired, and left heart catheterization was deferred per cardiology recommendations. While an ST-segment elevation due to occlusive myocardial infarction is a diagnosis that cannot be missed and requires an emergent workup, it is important to be aware that it is possible for a small bowel obstruction (SBO) to present with ECG changes consistent with an ST-segment elevation myocardial infarction (STEMI). We also found that ST-segment elevations due to obstructive intraabdominal pathology are more reportedly seen in the literature in the inferior leads than any other contiguous leads, which is a novel pattern not discussed in past literature.